2004
DOI: 10.1021/la040109a
|View full text |Cite
|
Sign up to set email alerts
|

Local Environment and Property of Water inside the Hollow Cylinder of a Lipid Nanotube

Abstract: We investigated the local environment of water confined inside the hollow cylinder of lipid nanotubes (LNTs) by time-resolved fluorescent measurements and attenuated-total-reflectance infrared (ATR-IR) spectroscopy. The LNT was obtained by self-assembly of cardanyl glucosides in water at room temperature and had an open-ended cylindrical nanospace with a diameter of 10-15 nm, a length of 10-100 microm, and hydrophilic inner and outer surfaces. We introduced a fluorescent probe of 8-anilinonaphthalene-1-sulfona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
68
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 64 publications
(71 citation statements)
references
References 58 publications
3
68
0
Order By: Relevance
“…60 Furthermore, confined water in the LNT hollow cylinder of 4 with 10 nm inner diameters proved to exhibit the physical properties of structured water similar to intracellular water. 61,62 In our early work, we found that capillary action enables the LNTs to encapsulate aqueous solutions or dispersions containing such guest substances into their internal hollow cylinders. [63][64][65] Thus, the self-assembled LNTs from 5 or 6 (Scheme 1) have been observed to encapsulate a variety of biomacromolecules, such as cadmium sulfide (2À3 nm) [ Fig.…”
Section: Hollow Cylinders That Can Encapsulate Biomacromolecular Guestsmentioning
confidence: 99%
See 1 more Smart Citation
“…60 Furthermore, confined water in the LNT hollow cylinder of 4 with 10 nm inner diameters proved to exhibit the physical properties of structured water similar to intracellular water. 61,62 In our early work, we found that capillary action enables the LNTs to encapsulate aqueous solutions or dispersions containing such guest substances into their internal hollow cylinders. [63][64][65] Thus, the self-assembled LNTs from 5 or 6 (Scheme 1) have been observed to encapsulate a variety of biomacromolecules, such as cadmium sulfide (2À3 nm) [ Fig.…”
Section: Hollow Cylinders That Can Encapsulate Biomacromolecular Guestsmentioning
confidence: 99%
“…76,77 This theoretical D-value is well compatible with our experimental results for the solid-state organic nanochannels with two open ends. We can envisage several possible causes for the relatively smaller D values: electrostatic attraction between charged surfaces of the nanotube and guest, 51,53 relatively larger viscosity of the confined water, 61 and diffusion in a restricted geometry. 5 …”
Section: Restricted Diffusion Of Biomacromolecular Guests In a Nanochmentioning
confidence: 99%
“…It is known that materials confined in nanospaces show structures and/or dynamics different from those exhibited in bulk. [1][2][3][4][5][6][7][8][9][10][11] Such unusual properties, which become more apparent as the size of the space decreases, partly come from the effects of the walls surrounding the spaces. 2,6 The interaction of compounds with the wall becomes more dominant with decreasing size of the space.…”
Section: Introductionmentioning
confidence: 99%
“…90 The viscosity of the confined water shows 3-4 cP, corresponding to that of bulk water at À20 C. That value is 3-4 times as large as that of water at room temperature. Thus, the water in geometrically confined nanospace displays many unique properties different from general bulk water.…”
Section: Unique Properties and Encapsulation Functions Of Hollow Cylimentioning
confidence: 89%
“…Thus, the water in geometrically confined nanospace displays many unique properties different from general bulk water. 90,91 Furthermore, the self-assembled nanotubes from 13 displayed a novel function, encapsulating guest substances with 10-50 nm dimensions into the nanochannel shaped by the hollow cylinders. In particular, capillary action allows us to effectively fill the nanotubes with, for example, gold nanoparticles (1-50 nm), 92,93 cadmium sulfide (2-3 nm), 87 magnetite (ca.…”
Section: Unique Properties and Encapsulation Functions Of Hollow Cylimentioning
confidence: 99%